Alterations in Bile Acid Metabolism Associated With Inflammatory Bowel Disease. Issue 9 (5th January 2021) - Li, Na; Zhan, Shukai; Tian, Zhenyi; Liu, Caiguang; Xie, Zonglin; Zhang, Shenghong; Chen, Minhu; Zeng, Zhirong; Zhuang, Xiaojun
Abstract: Inflammatory bowel disease (IBD) is a chronic relapsing inflammatory disorder closely related to gut dysbiosis, which is associated with alterations in an important bacterial metabolite, bile acids (BAs). Although certain findings pertinent to BA changes in IBD vary among studies owing to the differences in sample type, quantitated BA species, study methodology, and patient characteristics, a specific trend concerning variations of BAs in IBD has been identified. In elaborating on this observation, it was noted that primary BAs and conjugated BAs are augmented in fecal samples but there is a reduction in secondary BAs in fecal samples. It is not entirely clear why patients with IBD manifest these changes and what role these changes play in the onset and development of IBD. Previous studies have shown that IBD-associated BA changes may be caused by alterations in BA absorption, synthesis, and bacterial modification. The complex relationship between bacteria and BAs may provide additional and deeper insight into host-gut microbiota interactions in the pathogenesis of IBD. The characteristic BA changes may generate profound effects in patients with IBD by shaping the gut microbiota community, affecting inflammatory processes, causing BA malabsorption associated with diarrhea, and even leading to intestinal dysplasia and cancer. Thus, therapeutic strategies correcting the alterations in the composition of BAs, including the elimination of excess BAs and the supplementation of deficient BAs, may prove promising in IBD.